2020
DOI: 10.1093/ee/nvaa140
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal ofPhilaenus spumarius(Hemiptera: Aphrophoridae), a Vector ofXylella fastidiosa, in Olive Grove and Meadow Agroecosystems

Abstract: The introduction of the Xylella fastidiosa Wells bacterium into Apulia (South Italy) has caused the massive dieback of olive trees, and is threatening olive production throughout the Mediterranean Region. The key vector of X. fastidiosa in Europe is the spittlebug Philaenus spumarius L. The dispersal capabilities of P. spumarius are poorly known, despite being a key parameter for the prediction of the spread of the bacterium. In this study, we have examined the dispersal of P. spumarius adults in two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 78 publications
1
34
2
1
Order By: Relevance
“…Our results suggest that N. campestris is able to travel more than 2000 m in 35 days. These results contrast with those obtained by Bodino et al., (2020) who estimated that 98% of the P. spumarius population moved within a radius of 400 m. However, they did not specify the distance moved by the remaining 2% of the population. One of the limitations of the MMR techniques is that a very high sampling effort is needed to recover marked insects at long distances from the release point.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Our results suggest that N. campestris is able to travel more than 2000 m in 35 days. These results contrast with those obtained by Bodino et al., (2020) who estimated that 98% of the P. spumarius population moved within a radius of 400 m. However, they did not specify the distance moved by the remaining 2% of the population. One of the limitations of the MMR techniques is that a very high sampling effort is needed to recover marked insects at long distances from the release point.…”
Section: Discussioncontrasting
confidence: 95%
“…Bodino et al. (2020) performed a MMR study in southern Italy, sampling in concentric circles from 10 to 120 m from the released point. They estimated 98% of P. spumarius population disperse in a radius of 400 m. In contrast, Conyers et al (2020) found that the maximum distance moved by P. spumarius was 10 m in two days.…”
Section: Introductionmentioning
confidence: 99%
“…The species is naturally transmitted by xylem sap-feeding insects. The natural spread of X. fastidiosa depends on these insects, which can propagate the disease from plant to plant depending on their dispersal capability and transmission efficiency (Bodino et al 2020). Human-assisted spread is mainly driven by the movement of infected plant materials (EFSA 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, froghoppers represent the key vectors for the Xylella fastidiosa Wells bacterium, which led to a dramatic epidemic disease on olive trees in the Mediterranean area [12]. The dispersal capabilities of froghoppers are still not very well known and a recent field study has shown that they could be more effective than expected [13]. A deeper understanding of the key factors that lead to the effectiveness of dispersion of froghoppers could help the identification of strategies to mitigate the fast spread of the dieback of olive trees.…”
Section: Introductionmentioning
confidence: 99%